COST OF ILLNESS STROKE TREATMENT: A SYSTEMATIC REVIEW - Izzah, Raihana Nurul; Alia, Dina Fatma; Amalia, Annora Rizky; Sari, Yunita Dian Permata (Tahta Media Group, 2026)
Cardiovascular disease remains the leading cause of death worldwide, with stroke playing a significant role in increasing morbidity, mortality, and the global economic burden. This study aimed to systematically review the cost of illness and health expenditure associated with stroke across different countries. A systematic review was conducted using PubMed, ScienceDirect, and Springer databases for articles published between 2021 and 2026, following PRISMA guidelines. Studies included in the criteria were original research that reported direct and/or indirect costs due to stroke, both in primary health care facilities and in hospitals. Data extraction, screening, and quality assessment were performed using the CHEERS checklist. A total of 13 studies met the inclusion criteria. The findings showed that most studies (76%) applied the Cost Of Illness (COI) approach, while the rest used Health Expenditure (HE) methods. Direct medical costs, particularly those from inpatient care, constitute the largest component of stroke-related expenditures. Cost estimates show considerable variation between countries, with expenditures tending to be higher in high-income countries than in middle-income countries. Clinical severity, length of hospital stay, stroke subtype, and sociodemographic factors were identified as key determinants influencing total costs. Indirect cost components such as lost productivity and premature death also contribute significantly, but their reporting has not been consistent across studies. In conclusion, stroke imposes a substantial and heterogeneous economic burden influenced by methodological approaches, perspectives, and healthcare system differences. Comprehensive evaluation including both direct and indirect costs is essential to support effective health policy and resource allocation.